Infection-Derived Monocytic MDSCs Require TGF-β to Suppress Filarial-Specific IFN-γ But Not IL-13 Release by Filarial-Specific CD4+ T Cells In Vitro - Tamadaho, Ruth S. E.; Ritter, Manuel; Wiszniewsky, Anna; Arndts, Kathrin; Mack, Matthias; Hoerauf, Achim; Layland, Laura E. (Frontiers in Tropical Diseases, 2022)
Lymphatic filariasis (LF) remains a major health problem with severe economic repercussions in endemic communities of Sub-saharan Africa, South-East Asia and South America. The rodent-specific nematode Litomosoides sigmodontis (Ls) is used to study the immunomodulatory potential of filariae and research has elucidated pathways involving regulatory T cells (Tregs), IL-10 producing cells and alternatively activated macrophages (AAMs) and that CD4+ T cells play a paramount role during infection. Myeloid-derived suppressor cells (MDSCs) have been identified and characterised in man in cancer and other pathologies. The hallmark of MDSC populations is the suppression of T and B cell responses using various mechanisms, which are mostly specific to the pathology or setting. However, until now, it remains unclear whether they play a role in filarial-specific responses. We report here that monocytic MDSCs (Mo-MDSCs, CD11b+Ly6C+Ly6G-) and polymorphonuclear MDSCs (PMN-MDSCs, CD11b+Ly6Cint/loLy6G+) expanded in the thoracic cavity (TC, the site of infection) and correlated positively with filarial life-stages in Ls-infected BALB/c mice. In vitro, only infection-derived Mo-MDSCs showed a suppressive nature by preventing IL-13 and IFN-γ secretion from filarial-specific CD4+ T cells upon co-culture with soluble worm extract. This suppression was not mediated by IL-10, IL-6 or TNF-α, and did not require cell-contact, nitric oxide (NO), IL-4/IL-5 signalling pathways or CCR2. Interestingly, neutralizing TGF-β significantly rescued IFN-γ but not IL-13 production by filarial-specific CD4+ T cells. In comparison to naive cells, PCR array data showed an overall down-regulation of inflammatory pathways in both infection-derived Mo-MDSCs and PMN-MDSCs. In conclusion, these primary data sets show activity and expansion of MDSCs during Ls infection adding this regulatory cell type to the complex milieu of host responses during chronic helminth infections.